2023
DOI: 10.3389/fnins.2023.1163111
|View full text |Cite
|
Sign up to set email alerts
|

Functional and effective connectivity analysis of drug-resistant epilepsy: a resting-state fMRI analysis

Abstract: ObjectiveEpilepsy is considered as a neural network disorder. Seizure activity in epilepsy may disturb brain networks and damage brain functions. We propose using resting-state functional magnetic resonance imaging (rs-fMRI) data to characterize connectivity patterns in drug-resistant epilepsy.MethodsThis study enrolled 47 participants, including 28 with drug-resistant epilepsy and 19 healthy controls. Functional and effective connectivity was employed to assess drug-resistant epilepsy patients within resting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…A study validates the use of dynamic causal modeling (DCM) for resting state effective connectivity, which can detect early connectivity changes in neurodegenerative diseases ( Razi et al, 2015 ). In Bacon et al (2023) it is investigated how resting state effective and functional connectivity can help to understand the network disruptions caused by interictal discharges. Another study discusses how connectivity can reflect network reorganization and recovery following brain injury ( Nakamura et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study validates the use of dynamic causal modeling (DCM) for resting state effective connectivity, which can detect early connectivity changes in neurodegenerative diseases ( Razi et al, 2015 ). In Bacon et al (2023) it is investigated how resting state effective and functional connectivity can help to understand the network disruptions caused by interictal discharges. Another study discusses how connectivity can reflect network reorganization and recovery following brain injury ( Nakamura et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Electric field modelling results suggested that under Nettle™'s stimulation protocol, the majority of the electric field strength is concentrated in the mPFC, with secondary locations in the DLPFC and motor cortices) (Figure 1). Recent evidence suggested strong connections between the mPFC and the posterior cingulate and insula [11], which may explain why even after a single cycle use, users could expect to experience clinically significant results.…”
Section: A Electrical Field Modellingmentioning
confidence: 99%
“…Women with PD demonstrate heightened theta wave (4-7 Hz) activity in these pain-associated cerebral regions [3]. Similarly, women with severe premenstrual symptoms demonstrate alpha (8)(9)(10)(11)(12) wave asymmetry in the prefrontal regions of the brain [4]. The interrelation of pain with depressive and anxious states may be crucial for elucidating the role of theta and alpha activity in the sensory-emotional pain processing specific to PD.…”
Section: Introductionmentioning
confidence: 99%
“…DFC provides new insights into the pathological mechanisms of epilepsy ( Klugah-Brown et al, 2019 ). However, the influences of electrical stimulation on dFC in epilepsy are still not clear and are seldom explored ( Sawada et al, 2022 ; Bacon et al, 2023 ), which hinders the improvement of treatment effects.…”
Section: Introductionmentioning
confidence: 99%